A Comparative Study of Tree Imagery in David Jones’s Paintings and Poems in the Light of Panofsky’s Iconology - Houra Adel; Gholamreza Pirooz; Fataneh Mahmoudi; Gharibreza Gholamhosseinzade (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
David Jones, the British modern poet-painter, has exploited the elements of nature, particularly the motif of the tree, in both his verbal and visual language. Therefore, the current research, with a purposeful selection of Jones's paintings and poems "In Parenthesis" and "Anathemata", specifically focuses on the tree imagery present in both mediums. This research conducts a comparative and interdisciplinary study of these images based on Panofsky's theory of iconology.The results of the research show that Jones, as an "anti-modern" modernist, views the modern era as a detrimental factor leading to social and cultural decline, and he criticizes it. Through a poignant connection between the sufferings of Christ and those of contemporary humanity, Jones prompts reflection on modern cultural decadence and the potential for spiritual rejuvenation. He has approached the icon of the tree in paintings and poetry using various techniques of modern painting and poetry. In these images, the tree, with its existential quality, appears with all its rich mythological, historical, and religious past, acquiring symbolic value. In its most prominent symbolic form, the tree transforms into the cross, and the cross transforms into the suffering body of Christ. This wounded body of the tree forms the foundation of Jones's iconic semiotics.